NEED FOR SMART MOBILITY AND CHALLENGES AND OPPORTUNITIES FOR TRANSITIONING TOWARD IT IN CAR-DEPENDENT COUNTRIES: INSIGHTS FROM LITERATURE - Talal ALMAGHLOUTH; Uneb GAZDER; Osama ABUDAYYEH (Scientific Journal of Silesian University of Technology. Series Transport)
Car dependence is a trend brought about by the desire for comfortable transportation, in many countries around the world. After the invention and acceptance of automobiles, cities were designed with layouts that favored automobiles at the expense of other forms of transportation. However, the situation has changed with research and execution of plans for smart cities, with smart mobility transition taking centre stage. The purpose of this research is to highlight the need for transition to smart mobility, provide detailed description of various aspects of smart mobility and analyse the challenges and opportunities associated with the transition to smart mobility in car-dependent countries. A thorough and critical review of the literature has been done to achieve the aim of this study. Previous research efforts indicated that car-dependent cities have experienced several challenges in their transition to smart mobility, including inadequate infrastructure, low acceptance of new technological solutions, inadequate knowledge and framework for big data, financial constraints, data quality management, integration of data from different sources, privacy issues, and development of appropriate of government policies. There are several promising recommendations, which implementation is expected to help car-dependent countries overcome the above challenges and open opportunities for a successful transition. These recommendations include implementation of aggressive government policies, practicing greater inclusivity, and planning for the future of smart mobility by investing in Internet of Things (IoT) applications and reliable infrastructure. To facilitate the decision makers, challenges have been mapped with recommendations for transition to smart mobility, in light of the review findings.